Early 18F-FDG PET/CT Evaluation Shows Heterogeneous Metabolic Responses to Anti-EGFR Therapy in Patients with Metastatic Colorectal Cancer. - Erik J van Helden; Otto S Hoekstra; Ronald Boellaard; Chantal Roth; Emma R Mulder; Henk M W Verheul; C Willemien Menke-van der Houven van Oordt (PLoS ONE)
Objective The aim of this pilot study was to explore intrapatient mixed metabolic response and early 18F-FDG PET response evaluation using predefined quantification strategies in patients with advanced KRAS wild-type colorectal adenocarcinoma (mCRC) treated with cetuximab. Methods A 18F-FDG PET was performed at baseline and after 2 cycles of cetuximab. Metabolic response was categorized using thresholds suggested in PERCIST. Quantitative analysis was done for the sum of all target lesions, ≤ 5 lesions and the metabolically most active lesion per PET. Quantitative data were correlated with clinical benefit, according to RECIST v1.1, after two months of treatment. Results In nine evaluable patients the total number of target lesions was 34 (1-8 per patient). Mixed metabolic response was observed in three out of seven patients with multiple target lesions, using TLG. Dichotomised metabolic data of the sum of all or ≤ 5 lesions had a concordance with clinical benefit of 89% using SULmax or SULpeak, and 100% using TLG. Evaluating the metabolically most active lesion, concordance was 89% for all three units. Additionally, the decrease in TLG was significantly correlated with PFS for all three quantification strategies. Conclusion Mixed metabolic response was observed in nearly half of the patients with advanced KRAS wild-type mCRC treated with cetuximab. If ≤ 5 target lesions were evaluated using TLG clinical benefit was predicted correctly for all patients. Moreover, decrease in TLG is significantly correlated with the duration of PFS. Validation of these promising preliminary results in a larger cohort is currently on-going. Trial registration ClinicalTrials.gov NCT01691391.